Precise humidity control materials for autonomous regulation of indoor moisture - Qin, Menghao; Hou, Pumin; Wu, Zhimin; Wang, Juntao (Building and environment, 2020)
Indoor relative humidity is an important parameter to determine indoor air quality, occupants’ thermal comfort and building energy consumption. As recommended by ASHRAE, the appropriate indoor relative humidity range for a healthy and comfortable indoor environment is between 40% and 65% RH. In order to meet the requirements, the most commonly used method is mechanical dehumidification/humidification system by using electricity. However, this approach is energy consuming. In this paper, a novel precise humidity control material (PHCM) based on Metal-Organic Frameworks (MOFs) is synthesized and its application in built environment is investigated. This material has an S-shape isotherm, high porosity and very high water vapor uptake of 1.62 g/g at 80% RH. It can rapidly adsorb moisture as the indoor relative humidity exceeds 60%, and release moisture as relative humidity drops below 45%. Unlike the conventional desiccants, e.g. zeolites, silica gel etc., MOF-PHCM can autonomously control indoor relative humidity within the desired comfort range at room temperature. Hygrothermal properties of the new material are measured. Numerical simulations have been carried out to study the effect of MOF-PHCM on indoor hygrothermal conditions and building energy consumption in five different climates worldwide (i.e. hot desert, semi-arid, Mediterranean, temperate, and humid subtropical). The results show that MOF-PHCM can effectively control indoor relative humidity fluctuations and reduce building energy consumption in most climates without any additional energy input. MOF-PHCM can be easily regenerated by either night ventilation (e.g. in hot desert, semi-arid, Mediterranean climates) or heating system powered by low-grade energy (e.g. in humid climates). •The basic concept of Precise Humidity Control Material was proposed.•A new PHCM based on Metal-Organic Frames (MOFs) was synthesized.•MOF-PHCM has an operating RH range between 45% and 60%.•MOF-PHCM can effectively control indoor RH within the desired comfort range.•The regeneration temperature of MOF-PHCM is around 60 °C.